2022
DOI: 10.1175/jpo-d-21-0246.1
|View full text |Cite
|
Sign up to set email alerts
|

Drag Coefficient and Its Sea State Dependence under Tropical Cyclones

Abstract: The drag coefficient under tropical cyclones and its dependence on sea states are investigated by combining upper ocean current observations (using EM-APEX floats deployed under five tropical cyclones) and a coupled ocean-wave (Modular Ocean Model 6 - WAVEWATCH III) model. The estimated drag coefficient averaged over all storms is around 2−3×10−3 for wind speeds 25–55 m/s. While the drag coefficient weakly depends on wind speed in this wind speed range, it shows stronger dependence on sea states. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(52 citation statements)
references
References 36 publications
6
46
0
Order By: Relevance
“…This is supported by our data, which shows that COARE's wave dependent parameterization overestimates C D for alongshore wind and does not better predict observations than parameterization without waves (Figures 3 and 4). Similarly, Zhou et al (2022) found that, at high wind speeds, C D is significantly reduced when misalignment between the wind and dominant wave directions exceeds 45°. It is convictable that the complex wave systems created by tropical cyclones (e.g., Collins et al, 2018) can result in slanting-fetch like conditions limiting C D in some regions which will impact storm intensity.…”
Section: Results In Relation To Previous Researchmentioning
confidence: 76%
See 1 more Smart Citation
“…This is supported by our data, which shows that COARE's wave dependent parameterization overestimates C D for alongshore wind and does not better predict observations than parameterization without waves (Figures 3 and 4). Similarly, Zhou et al (2022) found that, at high wind speeds, C D is significantly reduced when misalignment between the wind and dominant wave directions exceeds 45°. It is convictable that the complex wave systems created by tropical cyclones (e.g., Collins et al, 2018) can result in slanting-fetch like conditions limiting C D in some regions which will impact storm intensity.…”
Section: Results In Relation To Previous Researchmentioning
confidence: 76%
“…Similarly, Zhou et al. (2022) found that, at high wind speeds, C D is significantly reduced when misalignment between the wind and dominant wave directions exceeds 45°. It is convictable that the complex wave systems created by tropical cyclones (e.g., Collins et al., 2018) can result in slanting‐fetch like conditions limiting C D in some regions which will impact storm intensity.…”
Section: Discussionmentioning
confidence: 76%
“…The uncertainty of wind stress is due to two factors: uncertainty of wind speed, and uncertainty of the drag coefficient. Zhou et al (2022) estimated the wind stress by matching the upper ocean current observations (from the EM-APEX floats) and model simulations under the same 5 TCs as in this study. They then estimated the mean drag coefficient based on a particular wind speed product (URI wind in Zhou et al (2022)) and the estimated wind stress.…”
Section: Wind Fieldsmentioning
confidence: 99%
“…Thus without addition information on C d , simulations of the upper ocean response to a particular storm may have significant errors in air-sea momentum flux. Following Sanford et al (2011) and Hsu et al (2017), Zhou et al (2022) have estimated the wind stress and drag coefficient by combining ocean current observations under 5 TCs and coupled ocean-wave model simulations. On the right to rear-right side of the storm, where wind and waves are aligned, the average C d ranges between 2.0 × 10 −3 and 3.0 × 10 −3 , and the stress is close to the downwind direction.…”
mentioning
confidence: 99%
“…We also note that we will compute the wind frictional velocity u * from 10‐m wind speed ( U 10 ) using the COARE3.5 drag coefficient (Edson et al., 2013). The drag coefficient itself could also be parameterized as a function of the sea state (making the non‐breaking transfer velocity also a sea‐state dependent term), but we choose to not consider this effect here to simplify our analysis and due to remaining uncertainty in the sea state dependence of drag coefficients (e.g., Sauvage et al., 2023; Zhou et al., 2022), in particular in high wind speed conditions, or mixed seas conditions.…”
Section: Gas Transfer Velocity Modelmentioning
confidence: 99%